Board Gender Equality in the Context of Corporate Market Value of Listed Firms in Nigeria - John Okon, Idorenyin; Atanda, Olabamiji; Anietimfon, Kenneth William (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The study investigates board gender diversity and firm value by employing samples from listed manufacturing firms in Nigeria between the periods of 2012-2021. This study is based on an ex-post facto research and data was collected from the annual report of 46 listed manufacturing firms on the Nigerian Exchange Group. To enhance the robustness of our results, we measure firm value in terms of share price and Tobin Q. Specifically, to control the model’s goodness of fit, the study employed the variable of foreign ownership and firm size. Overall, the empirical findings of this study are mixed in proving the effect of board gender diversity on firm value in Nigeria. Specifically, the study concludes that board gender diversity significantly decreases the firm value of listed manufacturing firms in Nigeria when measured in terms of Tobin Q but insignificantly decrease firm value when measured in terms of share price. We also conclude that foreign ownership insignificantly improves the firm value of listed manufacturing firms in Nigeria when measured in terms of Tobin Q but insignificantly decrease firm value when measured in terms of share price. In terms of gender diversity, our result illustrates that Nigeria’s efforts to promote gender equality and empower women are on the right track. Hence, higher proportion of women on board can facilitate communication and hence, improve performance. Finally, we conclude that foreign ownership significantly reduces the relationship between board gender diversity and the value of listed manufacturing firms in Nigeria when measured in terms of Tobin and share price.